A gnose junguiana: estudo das noções de corpo e mente em Jung e suas raízes no gnosticismo - Quintana, Carlos Bein (2009)
With this work we intend to show the links between the Jungian notions of body and mind with their corresponding in the Gnosticism. With this purpose, in the first part of this work we will develop a systematic exposition of the contemporary knowledge about Gnosticism, giving special attention to the body and mind. In the second part we will discuss the influences of Gnosticism upon the writings of C. G. Jung, as well as the adequacy of the expression Jungian Gnosis, discussing about its translation into the Jungian notions of body and mind. Finally, we will examine the supposed religious character of the Jungian theory and the possibilities to consider it a heretical doctrine